The Social and Economic Consequences of the First Year of Russia’s Fullscale Invasion of Ukraine - Mostepaniuk, Alla (Comparative Economic Research. Central and Eastern Europe, 2025)
This study aims to develop an analytical framework for understanding the social and economic outcomes of Russia’s military invasion of Ukraine by studying its impact on the labor market and migration, the economy and trade, social capital, and volunteering in Ukraine. The main economic and social consequences include the following: the massive out-migration of refugees and internally displaced people; the change in demographic structure; the relocation and reopening of businesses and adapting to new conditions; the total collapse and de-industrialization of the occupied territories’ economy; the interruption of supply chains; the reduction in trade volumes; the accumulation of social capital; and the development and spread of citizens’ volunteer cooperation to solve urgent issues at the national and local community levels. This study is limited to the available data and the effects on Ukraine’s economy and social sphere, excluding the impacts on the economies of European Union countries and the world economy in general.